Coastal subsidence detected by Synthetic Aperture Radar interferometry and its effects coupled with future sea‐level rise: the case of the Sele Plain (Southern Italy). Issue 2 (14th June 2017) - Di Paola, G.; Alberico, I.; Aucelli, P.P.C.; Matano, F.; Rizzo, A.; Vilardo, G.
Abstract : The amount of coastal subsidence on the Sele River coastal plain has been examined and measured with local vertical land movement data. The vertical displacements, derived by satellite radar differential interferometry processing (Ps‐InSAR), show that the analysed coastal sector is characterised by a south‐eastward decrease of vertical subsidence rates. These results have been coupled with sea‐level rise (SLR) scenarios, in order to identify the most critical areas. In general, the subsidence mostly affects areas where alluvial deposits are thicker, the back‐dune areas and the Sele River mouth, all late Holocene in age. Five local SLR scenarios allow identifying zones in the plain potentially prone to inundation and the shoreline retreat for the years 2065 and 2100. For these dates, 2.2% and 7.06% of the investigated area will have a topography lower than the estimated future sea level. Moreover, results show that the extent of the areas potentially exposed to inundation and erosion increases moving from south to north.